Algae : an introduction to phycology - Hoek, C. van den (Christiaan) (Cambridge University Press, 1995)
Algae are ubiquitous; a multitude of species ranging from microscopic unicells to gigantic kelps inhabit the world's oceans, freshwater bodies, soils, rocks, and trees, and are responsible for most of the global production of organic matter by photosynthesis. They thus play a fundamental role in the world's ecosystems and a reliable and modern introduction to their kaleidoscopic diversity, systematics, and phylogeny is indispensable. In this textbook, the main groups of algae (divisions or phyla) are considered in turn. Each chapter begins with a summary of the principal characteristics of the group and interesting aspects of ecology and evolution. The final chapter is a synthesis, in which the phylogeny of the algae is discussed in relation to the evolution of other living organisms, primarily on the basis of evidence from recent molecular studies. This book is the completely revised and updated edition of a highly acclaimed German work, which was heralded for its clarity as well as its breadth and depth of information. This new edition takes into account recent reevaluations in algal systematics and phylogeny provided by the powerful techniques of molecular genetics and electron microscopy, as well as more traditional life history studies. The book will be appropriate as an undergraduate text and as a reference for professionals in the field.